Assessment for paleoclimatic utility of biomass burning tracers in SE-Dome ice core, Greenland. (January 2019) - Parvin, Fahmida; Seki, Osamu; Fujita, Koji; Iizuka, Yoshinori; Matoba, Sumito; Ando, Takuto; Sawada, Ken
Abstract: We provide continuous records of biomass burning molecular tracers (levoglucosan and dehydroabietic acid) in a Greenland ice core collected from the Southeastern Dome (the SE-Dome ice core) over the past several decades to assess the paleoclimatic utility of these tracers in Greenland ice cores. An air mass backward-trajectory analysis indicates that eastern Canada is likely the primary source region of the biomass burning tracers. Comparisons of levoglucosan and dehydroabietic acid data in the SE-Dome ice core and area burned (vegetation fire) events in Canada suggests that the biomass burning tracers in the ice core document most of the pronounced biomass burning events in eastern Canada over the past several decades, confirming that analyses of biomass burning molecular tracers in Greenland ice cores are useful to reconstruct the frequency of significant biomass burning events in a local region. However, our study also highlights that the wind pattern when the biomass burning occurs is decisive for the registration of a biomass burning event in an ice core even though long-term changes in the wind regime associated with decadal-scale climate oscillations do not significantly influence the transport and deposition of biomass burning tracers on the Greenland ice sheet. Highlights: We investigate biomass burning tracers (levoglucosan and dehydroabietic acid). Generated ice core records of the biomass burning tracers over the last 60 years. Eastern Canada is likely the main source region of the biomass burning tracers. Biomass burning tracers document most of biomass burning events in eastern Canada. Climate oscillations do not significantly influence atmospheric transport of tracers.